Implementation of Forecasting Sales of Electronic Goods Using the Semi Average Method at Alex Electronics Store - Merwin Afrizal; Siswanto Siswanto; Aji Sudarsono (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2023)
Alex Electronics Store is one of the Electronics Stores in Kepahiang. So far, the sales system at the Alek Elektronik Store is still done manually where every sale will be made a sales note that will be given to consumers, and then a recapitulation is made at the end of the month how many items are sold at the Alex Elektronik Store. In addition, the shop owner checks regularly by looking at the remaining inventory one by one, if the remaining electronic goods are less than 10, purchases will be made to increase the existing stock. However, this takes quite a long time, and the store only sees the remaining stock of goods at the end of the month, and the large number of items in the store makes it difficult for the store to determine the amount to buy, because it does not see sales data that occurred during the previous few months. Implementation of forecasting sales of electronic goods using the Semi Average Method at the Alex Elektronik Store is used to provide information on the results of forecasting the number of sales of electronic goods in each forecast month based on data analysis of the number of sales of electronic goods for the last 12 months. In this study, a supporting application was built by implementing the Semi Average Method in it so that the forecasting process for sales of electronic goods can be easily used. With this application, it can provide information to the owner of the Alex Electronics Store so that he can manage the availability of electronic goods in the store by looking at the results of the sales forecast of electronic goods in the following year, thus avoiding errors in the management of the availability of electronic goods. Based on testing using the MAPE method, the results of the accuracy of forecasting using MAPE are obtained, it is concluded that the MAPE value obtained is 96.67%..